2013
DOI: 10.1016/j.bmcl.2013.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Novel ROS-activated agents utilize a tethered amine to selectively target acute myeloid leukemia

Abstract: This study explores the possible use of reactive oxygen-activated DNA modifying agents against acute myeloid leukemia (AML). A key amine on the lead agent was investigated via cytotoxicity assays and was found necessary for potency. The two best compounds were screened via the NCI-60 cell panel. These two compounds had potency between 200 and 800 nM against many of the leukemia cancer cell types. Subsequent experiments explored activity against a transformed AML model that mimics the molecular signatures ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Cytotoxicity analysis was carried out as previously described. [6] All R values were greater than 0.98, and standard errors of the three biological replicates were less than 20%. Unless otherwise stated, all RAC1 incubations occurred at 2 µ m for 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity analysis was carried out as previously described. [6] All R values were greater than 0.98, and standard errors of the three biological replicates were less than 20%. Unless otherwise stated, all RAC1 incubations occurred at 2 µ m for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…[5] We used an alternative and complementary approach based on selective activation by reactive oxygen species (ROS) to design next-generation smart DNA modifiers, termed ROS-activated cytotoxic agents (RACs). [6, 7] In this manuscript, we investigate the role and mechanism of DNA repair in treated cells to better understand the DNA modifying action of these novel RAC agents (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…135,136 We have shown that one agent is highly active and selective toward leukemia cells. Biochemical evaluation of these leukemia cells showed that levels of the catalase antioxidant enzyme are reduced compared to those of untransformed cells.…”
Section: Ros-targeted Anticancer Agentsmentioning
confidence: 99%
“…In this manuscript we have designed novel pro-drugs that are unreactive until oxidized by hydrogen peroxide. Once oxidized, the molecules, like the two natural products, are capable of a conjugate addition reaction 9,19 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent manuscript shows that induction of novel adducts changes anti-cancer activity and targets cancers 22 . The previous agents we designed possess mid-nanomolar activity against some tumor cells and up to 10-fold selectivity for AML cells 8,9 . Upon oxidation, the compound reacts by 1,2-addition with an amine identified as essential.…”
Section: Introductionmentioning
confidence: 99%